2013
DOI: 10.1177/1748895813500154
|View full text |Cite
|
Sign up to set email alerts
|

Strategic in/visibility: Does agency make sex workers invisible?

Abstract: This article examines the links between in/visibility, agency and mobility through the narratives of 55 predominantly indoor sex workers interviewed in Melbourne, Australia, where state government regulations permit some forms of sex work under a licensing framework. This article explores the tensions around the requirement for visibility in the regulation of sex work, the utility of 'strategic' invisibility in the lived realities of sex work and the discursive 'invisibilizing' of sex workers' agency in anti-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 39 publications
2
28
0
3
Order By: Relevance
“…Studies showed how registration and mandatory testing necessitated more frequent contact with healthcare systems [100,108,115,132] and were viewed positively by authors in Nevada, US, as a way of maintaining a low level of STIs [100] and by some sex workers as a form of self-responsibility for health [108,126]. However, in Guatemala the decision to comply with testing requirements was mostly motivated by fear of police harassment and detention rather than health considerations [126,132].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed how registration and mandatory testing necessitated more frequent contact with healthcare systems [100,108,115,132] and were viewed positively by authors in Nevada, US, as a way of maintaining a low level of STIs [100] and by some sex workers as a form of self-responsibility for health [108,126]. However, in Guatemala the decision to comply with testing requirements was mostly motivated by fear of police harassment and detention rather than health considerations [126,132].…”
Section: Resultsmentioning
confidence: 99%
“…However, in Guatemala the decision to comply with testing requirements was mostly motivated by fear of police harassment and detention rather than health considerations [126,132]. In Turkey, unregistered migrant sex workers were forcibly tested upon arrest [107], and in Australia, some sex workers experienced judgement and were refused testing by health professionals [108]. Mandatory testing of sex workers is considered a rights violation by the UN Refugee Agency and the Joint United Nations Programme on HIV/AIDS that can create barriers to sex workers accessing voluntary services and can facilitate discrimination against sex workers living with HIV.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, HRSWs are agents whose maneuverings through the city result in actions that allow them to keep in balance their private and work lives. While Ham and Gerard (2014), rightfully conclude that strategic invisibility is an agentic strategy that prevents experiencing or confronting the outcomes of stigma, it nonetheless has its limits. Paradoxically, maintaining invisibility through mobility simultaneously creates social and political immobility.…”
Section: Working 9-5: Everyday Invisible Mobilitiesmentioning
confidence: 99%
“…This has been proven to be a fallacy, with sex workers ranging from their teens all the way through to their seventies and eighties (Ham & Gerard, 2014). Recently the media has run a number of articles about more mature sex workers, including 'It's just like working in the Post Office!'…”
Section: Age Of Sex Workersmentioning
confidence: 99%